Big Books as A Learning Media in Literacy Activities of Students at MIN 1 Banyumas - Chasanah, Maghfirotun; Ningsih, Tutuk (International Proceedings of Nusantara Raya, 2023)
Due to the Covid-19 pandemic, many students in grades I and II could not read. Grades III and IV stuttered at reading or were not fluent and even had the same abilities as students in grade II before the pandemic. Many grades V and VI do not understand the reading text and the information conveyed in the text. The skills to read and understand information are part of literacy. One way to strengthen literacy is through the use of literacy media in the learning process in the classroom. The learning media used is Big Book. Through media literacy, teachers can increase student interest and condition active student participation. This research includes qualitative research. The approach used in this study is a qualitative approach that seeks to collect and process and even analyze and define data qualitatively. The results of this study stated that the beginning reading skills of class I and II students could be increased by using big book media. This is evidenced by the average value of students' initial reading and writing skills after the action increased. For students in grades III to VI, the success of learning using big book media can be seen through the ability to read that is no longer stammering and getting fluent. Students understand the purpose of reading and can answer questions related to reading and can retell the contents of reading